Correlation of vascularization and inflammation with severity of oral leukoplakia - Fatemeh Mashhadiabbas; Masoume Fayazi-Boroujeni (Iranian Society of Pathology, 2017)
Background & objective: Changes in submucosal vascularization and inflammation, determined by immunohistochemistry staining, were shown to be correlated with the development of dysplasia and invasiveness of epithelial cells in premalignant and malignant lesions. This study evaluated changes in sections routinely stained with Hematoxylin and Eosin (H&E) in order to investigate vascular density and intensity of inflammatory cells infiltration during the progression of oral leukoplakia with mild dysplasia to Squamous Cell Carcinoma (SCC).The aim of the research was to determine whether changes in sub-mucosal vascularity and inflammatory infiltration of leukoplakia in routine H&E-stained sections could contribute to the assessment of severity of the lesion. Methods: In this cross-sectional, comparative and descriptive study, vascular density and inflammation intensity of 125 available samples of H&E-stained sections, consisting of 35 cases of mild and moderate dysplasia, 38 severe dysplasia and carcinoma in situ, and 52 SCC, were investigated. To analyze the data, chi-square test, Mann-Whitney test, Kruskal-Wallis test, Tukey's post hoc test, and cumulative ordinal logistic regression were conducted. Results: There was a significantly higher vascular density in cases with severe dysplasia, in situ carcinoma, and SCC compared to those with mild to moderate dysplasia (P<0.0001). However, the difference in vascularity was not statically significant between severe dysplasia, carcinoma in situ, and SCC (P=0.78). Intensity of inflammatory cells infiltration in the underlying connective tissue was significantly different among the three groups (P<0.0001), and the highest intensity of inflammatory cells infiltration was seen in the SCC group. Conclusions: Increased submucosal vascularization and inflammatory cells infiltration can contribute further to predicting more aggressive epithelial dysplasia.